Reduced plastid genomes of colorless facultative pathogens Prototheca (Chlorophyta) are retained for membrane transport genes - Maciszewski, Kacper; Wilga, Gabriela; Jagielski, Tomasz; Bakuła, Zofia; Gawor, Jan; Gromadka, Robert; Karnkowska, Anna (BMC biology, 2024)
BACKGROUND: Plastids are usually involved in photosynthesis, but the secondary loss of this function is a widespread phenomenon in various lineages of algae and plants. In addition to the loss of genes associated with photosynthesis, the plastid genomes of colorless algae are frequently reduced further. To understand the pathways of reductive evolution associated with the loss of photosynthesis, it is necessary to study a number of closely related strains. Prototheca, a chlorophyte genus of facultative pathogens, provides an excellent opportunity to study this process with its well-sampled array of diverse colorless strains. RESULTS: We have sequenced the plastid genomes of 13 Prototheca strains and reconstructed a comprehensive phylogeny that reveals evolutionary patterns within the genus and among its closest relatives. Our phylogenomic analysis revealed three independent losses of photosynthesis among the Prototheca strains and varied protein-coding gene content in their ptDNA. Despite this diversity, all Prototheca strains retain the same key plastid functions. These include processes related to gene expression, as well as crucial roles in fatty acid and cysteine biosynthesis, and membrane transport. CONCLUSIONS: The retention of vestigial genomes in colorless plastids is typically associated with the biosynthesis of secondary metabolites. In contrast, the remarkable conservation of plastid membrane transport system components in the nonphotosynthetic genera Prototheca and Helicosporidium provides an additional constraint against the loss of ptDNA in this lineage. Furthermore, these genes can potentially serve as targets for therapeutic intervention, indicating their importance beyond the evolutionary context.
Keywords: Photosynthesis; Plastid genomes; Phylogeny; Chlorophyta; Genome, Plastid; genom plastidový; molekulární evoluce; Prototheca; Evolution, Molecular; Colorless plastids; fotosyntéza; fylogeneze